Between-game variation of physical soccer performance measures in highly trained youth soccer players - Doncaster, G.; Unnithan, V. (The Journal of Strength and Conditioning Research, 2019)
To assess the between-game variation in measures of physical performance during 11 vs. 11 soccer match play, over a short period, in highly trained youth soccer players. A single-cohort, observational, study design was used. Physical match performance data were collected from 17, male, highly trained, youth soccer players (age, 13.3 ± 0.4 years) over 3, 2 × 20 minutes, 11 vs. 11 matches. Using 10-Hz global positioning systems, the variables selected for analyses were total distance (TD), high-speed running (HSR), very high-speed running (VHSR), number of high-speed running efforts (HSReff), and number of very high-speed running efforts (VHSReff). Match data were also separated into cumulative 5-minute epochs, to identify the peak 5-minute epoch and the mean of the cumulative 5-minute epochs for each match. Variability was quantified using the coefficient of variation (CV), standard error of measurement, and intraclass correlation coefficient. Between- and within-player smallest worthwhile changes (SWC) were also calculated for each variable to aid in the interpretation of the data. Analysis of the variance between games reported a low CV for TD (3.8%) but larger CVs for HSR (33.3%), HSReff (35.4%), and VHSR and VHSReff (59.6 and 57.4%, respectively). Analysis of 5-minute epochs (peak and average) found an increase in the CVs beyond that of the values reported for the whole match. Between-player SWC in high-intensity physical performance data ranged from 24.7 to 42.4%, whereas within-player SWC ranged from 1.2 to 79.9%. The between-game variability of high-intensity and very high-intensity activities in youth soccer players, across 3 soccer matches over a short period (2 weeks), is relatively "large" and specific to the individual, thus highlighting the need for caution when interpreting physical performance data between games and players.